Development of weather-based empirical forecasting models of tomato leaf curl disease in Northern Mindanao, Philippines - Borja, Bernadith T. (Journal of ISSAAS, 2020)
Tomato leaf curl is a major virus disease in the Philippines. This study was conducted to develop and validate tomato leaf curl empirical forecasting models in Northern Mindanao. Tomato leaf curl disease incidence (%) and index (%) were assessed and number of whiteflies was counted per plant every two weeks after transplanting in the 2018 dry and wet seasons in field experiments in two sites: Malaybalay, Bukidnon and Claveria, Misamis Oriental. The relationships of disease incidence and index with whitefly number and biweekly-averaged weather variables were analyzed using linear correlation analysis. Disease incidence and index were positively correlated with minimum, maximum and average temperatures, but were positively and negatively correlated with relative humidity (RH), wind speed and rainfall in different sites and seasons. Whitefly number was negatively correlated with disease incidence and index in specific sites and seasons. Using stepwise multiple linear regression analyses, empirical models were developed that included temperature, RH, rainfall, wind speed and whitefly number that explained 90-94% of the variation in disease incidence. Multiple linear regression models specific to site and season were evaluated as good predictive models based on low average prediction error (MDIFF), and narrow length of prediction error (LPE).